A dynamic pricing model for Turkey's electricity distribution companies in the future Smart Grid infrastructure - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
Smart grids are a system in which the end user (customer, consumer or prosumer) takes an active role in the management of energy and that the energy flow is monitored / controlled in real time by bidirectional data communication, which incorporates advanced measurement infrastructures. The conclusive output of this system is the dynamic pricing of energy for demand response. This paper aims to present a sample dynamic pricing model using artificial neural network for energy distribution companies, utilities, aggregators and distribution system operators in the near future in Turkey. © 2019 IEEE.
Keywords: artificial neural network; demand response; dynamic pricing; smart grid